Sustainability Analysis of Beach and Mangrove Tourism in Clungup, Malang Regency of East Java - Agustina Eunike; Dewi Hardiningtyas; Silvie Indah Kartika Sari; Andronicus - (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Clungup is an area in Malang, East Java, which has good coastal and mangrove resources. It tends to be a potential tourism and has the opportunity as a tourist area. Readiness of managers and the surrounding community to manage the existing coastal resources is another reason. The combination of management, government and community and coastal resources, became the focus of this research using Multidimensional Scaling (MDS) analysis generated from RapTourism (Rapid Appraisal for Tourism) approach. The sustainability of resource management as an asset from tourism through three dimensional approaches, namely ecological, social, and management dimension. Rainfall, mangrove species diversity, community knowledge level of resources, community dependence on the region, interaction level between manager and stakeholders as the most sensitive attributes. Monte Carlo analysis shows that the ecological and management dimension are in stable stage, while for the social dimension is quite stable because it is very vulnerable to change. This study proposes four recommendations to maintain the sustainability of the tourism area in Clungup Beach. The recommendations include the regulations to manage the exploitation of coastal areas, an adequate infrastructure to support the safety of tourists, develop environmentally friendly tourism activities, and strict regulations in expanding tourism in the areas.